Molecular markers of benzene polycarboxylic acids in describing biochar physiochemical properties and sorption characteristics. (June 2018) - Chang, Zhaofeng; Tian, Luping; Wu, Min; Dong, Xudong; Peng, Juan; Pan, Bo
Abstract: Biochar function in soil is based on properties such as sorption characteristics, and these are expected to change throughout the life cycle of the biochar. Because biochar particles cannot easily be separated from soil particles, this change is seldom investigated. Biochar-related molecular markers, such as benzene polycarboxylic acids (BPCAs) are promising tools for studying the properties of biochars in complex environmental matrices. In this study, biochars were derived from corn straw and pine wood sawdust at 200–500 °C, and their aging was simulated with NaClO. Biochar properties were characterized by elemental analysis, BET surface characterization and BPCA molecular marker analysis. Chemical oxidation decreased the surface area (SA) but increased the O content of biochars. The oxidation decreased the amount of biochars, with a mass loss in the range of 10–55%. A similar mass loss was also observed for BPCAs and was negatively related to both the pyrolysis temperature and the extent of the condensed structure (higher aromaticity). The biochar amounts were calculated quantitatively using the sum of BPCA contents, with a conversion factor (the ratio of biochar amount to BPCA content) in the range of 3.3–5.5, and were negatively related to the B5CA content. Three model pollutants, namely, bisphenol A (BPA), sulfamethoxazole (SMX), and phenanthrene (PHE), were chosen to study the sorption characteristics of biochar before and after oxidation. Chemical oxidation generally increased SMX sorption but decreased PHE sorption. The nonlinear factor n, based on Freundlich equation modeling, was negatively related to B6CA for all three chemicals. The BPCA molecular markers, especially B5CA and B6CA, were correlated to the biochar properties before and after oxidation and are thus a potentially useful technique for describing the characteristics of biochar in the environment. Graphical abstract: Image 1 Highlights: NaClO oxidation results in 10–55% mass loss of the biochars. The conversion factor relating BPCA to biochar mass varies with pyrolysis degree. BPCA molecular marker composition does not change with chemical oxidation. Chemical oxidation generally increased SMX sorption, but decreased PHE sorption. The nonlinear factor n is negatively related to B6CA. Abstract : Molecular markers of benzene polycarboxylic acids can describe both the physiochemical properties and sorption characteristics of biochar.